Dramatic relapse of seizures after everolimus withdrawal. (January 2018) - Mingarelli, Alessia; Vignoli, Aglaia; La Briola, Francesca; Peron, Angela; Giordano, Lucio; Banderali, Giuseppe; Canevini, Maria Paola
Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant multisystemic disorder caused by deregulation of the mTOR pathway, and represents one of the leading genetic causes of epilepsy. mTOR inhibitors (Sirolimus and Everolimus) are currently approved only for the treatment of growing subependymal giant cell astrocytomas, renal angiomyolipomas and lymphangioleiomyomatosis in TSC. However, preclinical and clinical evidence supports their potential role in effectively treating TSC-associated epilepsy, but no consensus on its use in seizures has been reached yet and there are few data on epilepsy outcome after the suspension of mTOR inhibitors treatment. We report for the first time on a patient in whom discontinuation of Everolimus (prescribed for growing subependymal giant cell astrocytomas) was associated with a relapse of seizures twice, and control of seizures was regained after reintroducing the medicine. This clinical report supports the promising potential of Everolimus in treating epilepsy in TSC, and specifically underlines the non-permanent effect on seizures after withdrawal. Highlights: This case confirms the antiepileptogenic effect of mTOR inhibitors. They may have a non-permanent effect on seizures after withdrawal; antiepileptic effect may be regained after reintroduction. Caregivers should cautiously balance the decision of Everolimus withdrawal.